OVERVIEW OF KNOWLEDGE OF NURSES PREPAREDNESS IN HEALTH SERVICES IN FACING DISASTERS : LITERATURE REVIEW - Siregar, Aguansyah Maulana; Hasibuan, Abdurrozzaq (RADINKA JAYA UTAMA PUBLISHER, 2024)
A disaster is an event or situation that results in significant loss in terms of life, health, security, or the environment, as well as having a lasting impact on the community or environment in a region or location. Disaster preparedness is a crucial aspect in determining success in disaster management. This literature aims to identify a more comprehensive picture of the knowledge of hospital nursing preparedness in the face of disasters. Data collection by searching articles online using Google Scholar, Sage Journals, and Sciencedirect with year-to-year vulnerabilities 2019-2024. The study of literature review on 10 of the articles analysed showed that the majority of nurses have good categories of knowledge. The majority have good knowledge of the treatment of patients victims of disasters, including in flood disaster situations, evacuation, and prevention as well as fire management.